The enigmatic double-peaked stripped-envelope SN 2023aew - Kangas, T.; Kuncarayakti, H.; Nagao, T.; Kotak, R.; Kankare, E.; Fraser, M.; Stevance, H.; Mattila, S.; Maeda, K.; Stritzinger, M.; Lundqvist, P.; Elias-Rosa, N.; et al. (EDP Sciences, 2025)
We present optical and near-infrared photometry and spectroscopy of SN 2023aew and our findings on its remarkable properties. This event, initially resembling a Type IIb supernova (SN), rebrightens dramatically ~90 d after the first peak, at which time its spectrum transforms into that of a SN Ic. The slowly evolving spectrum specifically resembles a post-peak SN Ic with relatively low line velocities even during the second rise. The second peak, reached 119 d after the first peak, is both more luminous (Mr = -18.75±0.04 mag) and much broader than those of typical SNe Ic. Blackbody fits to SN 2023aew indicate that the photosphere shrinks almost throughout its observed evolution, and the second peak is caused by an increasing temperature. Bumps in the light curve after the second peak suggest interaction with circumstellar matter (CSM) or possibly accretion. We consider several scenarios for producing the unprecedented behavior of SN 2023aew. Two separate SNe, either unrelated or from the same binary system, require either an incredible coincidence or extreme fine-tuning. A pre-SN eruption followed by a SN requires an extremely powerful, SN-like eruption (consistent with ~1051 erg) and is also disfavored. We therefore consider only the first peak a true stellar explosion. The observed evolution is difficult to reproduce if the second peak is dominated by interaction with a distant CSM shell. A delayed internal heating mechanism is more likely, but emerging embedded interaction with a CSM disk should be accompanied by CSM lines in the spectrum, which are not observed, and is difficult to hide long enough. A magnetar central engine requires a delayed onset to explain the long time between the peaks. Delayed fallback accretion onto a black hole may present the most promising scenario, but we cannot definitively establish the power source.